2016
DOI: 10.1093/toxsci/kfw261
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure to volatile anesthetic isoflurane worsens the outcome of polymicrobial abdominal sepsis

Abstract: Sepsis continues to result in high morbidity and mortality. General anesthesia is often administered to septic patients, but the impacts of general anesthesia on host defense are not well understood. General anesthesia can be given by volatile and intravenous anesthetics. Our previous in vitro study showed that volatile anesthetic isoflurane directly inhibits leukocyte function-associated antigen-1 (LFA-1) and macrophage-1 antigen (Mac-1), critical adhesion molecules on leukocytes. Thus, the role of isoflurane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 48 publications
0
55
2
Order By: Relevance
“…The better survival of isofluraneor sevoflurane‐exposed group was presumably explained by the significant reduction of proinflammatory mediator levels by these volatile anesthetics. In contrast, our model used 2‐time puncture of the cecum and was not associated with the mortality within the first 48 h in WT mice (8). Our proinflammatory cytokine levels were not as elevated as in the aforementioned study (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The better survival of isofluraneor sevoflurane‐exposed group was presumably explained by the significant reduction of proinflammatory mediator levels by these volatile anesthetics. In contrast, our model used 2‐time puncture of the cecum and was not associated with the mortality within the first 48 h in WT mice (8). Our proinflammatory cytokine levels were not as elevated as in the aforementioned study (8).…”
Section: Discussionmentioning
confidence: 99%
“…All the experimental procedures complied with institutional and federal guidelines regarding the use of animals in research. Polymicrobial abdominal sepsis was induced by CLP, as we previously performed (8). In brief, mice were anesthetized with ketamine (60 mg/kg) and xylazine (5 mg/kg) given intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organ injury represents a main complication with significant morbidity and mortality, and overwhelming migration of activated neutrophils into organs and subsequent endothelial cell damage are mainly responsible [ 2 ]. Patients suffering from sepsis often undergo procedures or are sedated in intensive care unit (ICU) in Europe and Canada under volatile anesthetics [ 3 6 ]. A growing literature suggests that volatile anesthetics possess immunomodulatory effects [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…LFA-1 and Mac-1 are two major β2 integrins expressed constitutively on neutrophils, and interact with several ligands including a common ligand called intercellular adhesion molecule-1 (ICAM-1), which is constitutively expressed on the endothelial cells and some other cells [ 20 ]. We previously showed that commonly used volatile anesthetic isoflurane blocked both LFA-1 and Mac-1 on neutrophils [ 3 , 21 24 ]. Polymicrobial abdominal sepsis model induced by cecal ligation and puncture (CLP) surgery is the model widely used to study sepsis, recapitulating human sepsis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%